How to Promote Energy Transition With Market Design: A Review on China’s Electric Power Sector - Pingkuo, Liu; Pengbo, Gao; Chen, Zhang (Frontiers in Energy Research, 2021)
Energy transition, especially in the power industry, will lead to a significant promotion in energy sustainable development. Lots of emphases have been focused on the impact of policy on the energy transition; however, there were little studies on the role of the market. This paper will be devoted to the theoretical basis of market design comprehensively and discusses the obstacles restricting China’s energy transition by using an Institution-Economics-Technology-Behavior (IETB) analysis framework (four dimensions including Institution, Economics, Technology, and Behavior). In addition, the paper provides an overview of research findings on some available market designs related to the energy transition. Of note, power spot market, power capacity market, power futures market, carbon emission market, and Tradable Green Certificate (TGC) market are highlighted and discussed with emphasis. And the effects of implementing each market on overcoming those obstacles in the energy transition process are analyzed. The review results show that the market design is as important as the policy-making; hence, it is unwise for energy transition to focus on policies and ignore markets, and the market design should be pertinent and objective. Finally, some policy recommendations and market design suggestions are put forward.